Strategi Marketing Public Relation PT. JNE Express Pekanbaru dalam Meningkatkan Kualitas Terhadap Kepuasan Pelanggan - Nur Halim; Maal Abrar; Hanifahturahmi (CV Insan Kreasi Media, 2022)
The study, entitled strategy Marketing Public Relations in creating quality for JNE expedition customer satisfaction, the activities carried out by marketing public relations in order to create customer satisfaction In jne Pekanbaru.The aim of this study is to learn more about public relations and marketing strategies to find out what products and programs from JNE that customers remain loyal to the JNE expedition, and in order to create customer satisfaction using certain strategies. This study uses descriptive analysis to describe the problem of the creation of Marketing and Public relations strategy in creating customer satisfaction Online shop. This study uses data collection techniques, literature study, observation, interviews and documentation. The results of this study prove that the strategy of marketing public relations, with the Theory of Marketing Public Relations that strategy in JNE canbe well received by customers and can increase customer satisfaction.